Glaucoma Australia educational impact study: a randomized short‐term clinical trial evaluating the association between glaucoma education and patient knowledge, anxiety and treatment satisfaction. (11th August 2017) - Skalicky, Simon E; D'Mellow, Guy; House, Philip; Fenwick, Eva; ,
Abstract: Importance: Targeted education may impact glaucoma patients' clinical experience. Background: The aim of this study was to measure the impact of patient‐centred glaucoma‐related education on knowledge, anxiety and treatment satisfaction. Design: This was a multicentre Australia‐wide randomized clinical trial. Participants: One hundred one newly diagnosed glaucoma patients were randomized 1:1 to intervention or control groups. Methods: Those randomized to the Glaucoma Australia educational intervention received telephone‐based counselling about glaucoma followed by mail‐out information, in addition to usual care and information from their treating ophthalmologist. The control group received only usual care and information from their treating ophthalmologist. Surveys were administered at baseline and 4 weeks following intervention. Main Outcome Measures: The Auckland Glaucoma Knowledge Questionnaire measured glaucoma‐related knowledge. The Hospital Anxiety and Depression Scale and Eye‐Drop Satisfaction Questionnaire measured anxiety and patient treatment satisfaction, respectively. Results: Mean age was 64.7 ± 11.1 years, and 52 (51.5%) were male. There was no noticeable increase in knowledge levels in the control group (mean difference: 0.04 logits, P = 0.7), compared with a 0.49‐logit ( P = 0.02) increase in knowledge levels in the intervention group. Between‐group comparison showed a non‐significant increase in knowledge (0.45 logits, P = 0.07) comparing intervention participants with controls. Intervention participants experienced a statistically significant decrease in anxiety compared to controls (−0.60 logits, P = 0.02). No between‐group difference was found in Eye‐Drop Satisfaction Questionnaire scores. Conclusions and Relevance: Patient‐centred glaucoma‐related education and support services may improve knowledge and can reduce anxiety for newly diagnosed glaucoma patients. All glaucoma patients should be adequately counselled about the nature of the disease and its management.